Is Citation Analysis Feasible for Non-SCI Journals in the Absence of a Suitable Measuring Tool in Indian Context? - Sinha, S. C.; Dhiman, A. K. (Journal of Information and Knowledge, 2001)
Dr. Garfield's unique innovation of Science Citation Index (SCI) in the 60's is the only measuring tool of scientific research activities in the world. SCI has kept pace with growing scientific research outputs during the three and half decades, well expended almost in all scientific disciplines. India is the third largest country in Asia producing scientific literature in the farm of articles. Majority of scientists are actively engaged in research activities and are publishing their research output in the form of articles in Indian journals. Numerous national conferences are producing weal th of information in the form of papers presented in them. Many Indian scientists settled abroad are producing important articles being published in international journals covered by SCI and their achievements are praiseworthy. At present, only 10 Indian journals are covered by SCI; there is a prime need to evolve an alternative measuring tool. Authors face problems while trying to find out their citations. So there is a genuine need to develop an Indian Science Citation Index (ISCI) and Indian Social Science Citation Index (ISSCI).